Comparison of the Effectiveness of Digital Scrolling and Linear Text on UPI Student Information Retention - Fahrul Virgias; Aufa Akmal Haadi; Muhammad Aqbil Nashrul Ghaniy; Muhammad Fawwaz Al Fayyadh (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The digital transformation in education has led to a shift in reading formats, impacting cognitive processes and the way students absorb information. This study aims to examine and compare the effect of digital scrolling and linear text presentation formats on the level of information retention among students. This study employed a comparative quantitative method with a between-subject design. The research sample consisted of 20 active students of Universitas Pendidikan Indonesia (UPI) Bumi Siliwangi Campus, selected using the total sampling technique. The respondents were divided into two treatment groups and evaluated using a questionnaire instrument in the form of a closed-ended objective test with the same reading topic. Data analysis was conducted using the Independent Sample t-test and a robustness test using the Mann-Whitney U test. Descriptively, the research results showed that the linear text group had a higher average retention score (13.30) compared to the scrolling group (12.70). Nevertheless, hypothesis testing confirmed that there was no statistically significant difference between the two groups. The effect size test using Cohen's d yielded a value of 0.323 (small-to-medium category), indicating that the linear text format still provides a meaningful practical impact in supporting the reader's working memory due to text segmentation and more stable visual markers. In conclusion, it is assumed that students have equal adaptive capabilities in consuming both digital media formats; however, the linear text format is considered more optimal for reducing cognitive load.